Hubungan Indeks Massa Tubuh Dan Kecepatan Jalan Dengan Resiko Jatuh Pada Lanjut Usia - Utami, Frista Yuanita, Umi Budi Rahayu, S.Fis.,Ftr.,M.Kes, Dwi Rosella K, S.Fis.,Ftr.,M.Fis (2015)
The number of older people in Indonesia was growing. Aging in older people to be followed some degeneration. The degeneration happened in strength, flexibility and balance. The degeneration cab ne easy saw un physical degeneration such as reducing musle strength in extremity. It caused effect in balancing in older people and caused risk of fall. Number of samples at this research 67 samples, way of sampling applies method random sampling. BMI was measured using body weight and height, gait speed was measured using time and distance, risk fall was measured using Berg Balance Scale. Research desaign at this research is observasional research with cross sectional. The analysis this research is Spearman Rho because the data using categoric scale. Based on correlation test between BMI and risk fall obtained p 0,104 (p> 0,05) and coefisien correlation r 0,200 (r=0,200) which mean there is no relationship between BMI and risk fall and strength of correlation is small. Correlation test between gait speed and risk fall obtained p 0,123 (p> 0,05) and coefisien correlation r 0,190 (r=0,190)which mean there is no relationship gait speed and risk fall and strength of correlation is very small. Hopefully this research can continue and earns good for researcher, medical energy, and or common public.